Amino acids in piglet diarrhea: Effects, mechanisms and insights - Xihong Zhou; Jing Liang; Xia Xiong; Yulong Yin (Animal Nutrition, 2024)
Piglet diarrhea is among one of the most serious health problems faced by the pig industry, resulting in significant economic losses. Diarrheal disease in piglets has a multifactorial etiology that is affected by physiology, environment, and management strategy. Diarrhea is the most apparent symptom of intestinal dysfunction. As a key class of essential nutrients in the piglet diet, amino acids confer a variety of beneficial effects on piglets in addition to being used as a substrate for protein synthesis, including maintaining appropriate intestinal integrity, permeability and epithelial renewal, and alleviating morphological damage and inflammatory and oxidative stress. Thus, provision of appropriate levels of amino acids could alleviate piglet diarrhea. Most amino acid effects are mediated by metabolites, gut microbes, and related signaling pathways. In this review, we summarize the current understanding of dietary amino acid effects on gut health and diarrhea incidence in piglets, and reveal the mechanisms involved. We also provide ideas for using amino acid blends and emphasize the importance of amino acid balance in the diet to prevent diarrhea in piglets.